Chronic kidney disease in Asia – Protocol for a collaborative overview - Jha, V (Wiley, 2016)
Background The burden of chronic kidney disease (CKD) is growing rapidly around the world. However, there is limited information on the overall regional prevalence of CKD, as well as the prognostic implications and treatment patterns in Asian region. We have established the Asian Renal Collaboration (ARC) with the goal of consolidating region-wide data regarding CKD. Design and Methods This collaborative project will synthesize data and perform meta-analyses of observational studies conducted in Asia. Studies will be identified through a systematic literature search including abstracts, proceedings of meetings, electronic databases such as MEDLINE and EMBASE. Personal enquiry among collaborators and experts in the region will identify additional studies, or other data sources such as registries. Both cross-sectional and longitudinal studies that describe the prevalence of CKD and its complications will be included, as will longitudinal studies that describe important clinical outcomes for people with CKD. Individual participant data will be sought, where possible, from each of the studies included in the collaboration for baseline parameters and subsequent outcomes, in order to maximize flexibility and consistency of data analyses. Conclusions This study is an initiative offering a unique opportunity to obtain information about the prevalence and manifestations of CKD in Asia, as well as its risk factors. The ARC will also provide insights into important outcomes including progression of CKD, CKD complications, cardiovascular disease and death. These findings will improve our understanding of kidney disease in Asia, and thus help inform service provision, preventive care and further research across the region.